Application of artificial spawning substrates to support lacustrine fish recruitment and fisheries enhancement in a Chinese lake - Feng, Kai; Yuan, Jing; Zhang, Yinzhe; Qian, Jing; Liu, Jiashou; Li, Zhongjie; Lek, Sovan; Wang, Qidong (Frontiers in Ecology and Evolution, 2023)
Lake littoral zones with abundant submerged vegetation are considered to harbor diverse biotic communities and additionally serve as spawning grounds for important fishery resources. In recent decades, due to various human activities submerged vegetation in lakes have declined dramatically resulting in the function loss of spawning grounds. In order to enhance the recruitment of lacustrine fish (mainly Carassius auratus and Cyprinus carpio) and the proliferation of fishery resources, we explored a method of constructing artificial spawning ground based on artificial spawning substrate in lake. The results of present study indicate that the artificial substrates with complex and dense three-dimensional structure which have enough space to enable material exchange and oxygen circulation could be efficient to enhance fish recruitment. The water temperature of spawning peaks of artificial substrates were within the range of 20~25 ℃, and the water temperature provides a basis for the deployment period of artificial spawning grounds. The spawning substrate in the upper layer of water column was more attractive for fish to spawn. The above results provide guidance for the deployment of artificial spawning grounds from both temporal and spatial scales. Observations on the behavior of aggregations found that spawning activities mainly occurred at night and in the early morning. The abundance of larger individuals (>20cm), as potential spawning groups, increased during this period. The above findings are informative to the construction and management of artificial spawning ground in lakes.